PENGEMBANGAN LITERASI LINGKUGAN SEKOLAH BERBASIS KOLABORASI STAKE HOLDER SEBAGAI PILOTING PROJECT DI SEKOLAH DASAR - Parida, Lusila; Kurniati, Agusta (Universitas Nusantara PGRI Kediri, 2021)
Environmental literacy is an attitude of literacy or love of environment so that there is a responsibility to maintain the existence of all natural resources. Currently, environmental damage is getting worse, so a collaborative integrative strategy for schools is needed to develop environmental literacy with stakeholders. The purpose of this community service activity is to provide the knowledge, create the awareness and strengthen the empowerment of teachers, lecturers, students, staff and parents in order to realize the eco-school concept in elementary schools. The method of this collaborative activity is in the form of training for teachers and staff. It is implemented byplanting trees in the school environment as a starting point for realizing the concept of eco school in elementary schools. The real impacts of collaborative activities through community service activities are; (1). Introducing the concept of eco school as an alternative to realize environmental literacy in elementary schools (2). Expanding the knowledge and skills of teachers in designing environmental-based learning activities and school programs (3). Building collaboration in realizing an Environmental-based school through the Eco School concept at partner elementary schools.